Mechanism and application prospect of magnesium-based materials in cancer treatment - Yutong Ma; Yi Wang; Siwei Song; Xinyue Yu; Can Xu; Long Wan; Fan Yao; Ke Yang; Frank Witte; Shude Yang (Journal of Magnesium and Alloys)
Magnesium-based materials, including magnesium alloys, have emerged as a promising class of biodegradable materials with potential applications in cancer therapy due to their unique properties, including biocompatibility, biodegradability, and the ability to modulate the tumor microenvironment. The main degradation products of magnesium alloys are magnesium ions (Mg2+), hydrogen (H2), and magnesium hydroxide (Mg(OH)2). Magnesium ions can regulate tumor growth and metastasis by mediating the inflammatory response and oxidative stress, maintaining genomic stability, and affecting the tumor microenvironment. Similarly, hydrogen can inhibit tumorigenesis through antioxidant and anti-inflammatory properties. Moreover, Mg(OH)2 can alter the pH of the microenvironment, impacting tumorigenesis. Biodegradable magnesium alloys serve various functions in clinical applications, including, but not limited to, bone fixation, coronary stents, and drug carriers. Nonetheless, the anti-tumor mechanism associated with magnesium-based materials has not been thoroughly investigated. This review provides a comprehensive overview of the current state of magnesium-based therapies for cancer. It highlights the mechanisms of action, identifies the challenges that must be addressed, and discusses prospects for oncological applications.